A Rare Case Report of Idiopathic Abdominal Cocoon Presenting as Acute Intestinal Obstruction-Management Challenges - Sharma, Pawan; Nair, Vipin V.; Singh Rehsi, Simarjit; Singh, Vivek Kumar (Lietuvos chirurgija, 2021)
The idiopathic variant of sclerosing Intraperitoneal fibrosis is a rare pathological entity causing intestinal obstruction. Even though it is described since the beginning of the last century, we are still clueless about the aetiology of this problem. The presentation is often confusing and the clinical and laboratory values will be not confirmatory to establish a diagnosis. A Contrast-enhanced CT scan is a vital investigation of choice. Here we discuss a case of intestinal obstruction with a preop diagnosis of internal herniation, which turned out to be a case of massive intraperitoneal fibrosis. The histopathology was not significant, and no secondary cause was identified. The case report throws wisdom into the existence of this entity and how with a CT scan we can suspect it before surgery. With adequate and meticulous enterolysis we can surgically rehabilitate these patients so that they can lead a normal life.